Do private firms benefit from trading in the private securities market? - Robert Loveland; Eric Fricke; Sinan Goktan (The Journal of Entrepreneurial Finance (JEF), 2017)
The trading of private securities has recently gained greater visibility and importance with the advent of organized, private security exchanges. This paper uses data on IPO firms that list on the SharesPost private securities exchange platform to examine the potential benefits of a listing. Specifically, we test whether a listing reduces IPO underpricing or enables liquidity provision to firm employees. Controlling for endogeneity, we find no evidence that a pre-IPO listing on SharesPost lessens IPO underpricing. However, we also find that SharesPost-listed companies are able to pay their employees less in cash and more in stock and stock options than comparable non-SharesPost companies. Further, executive officers in SharesPost-listed IPO companies sell less shares during the IPO. These findings suggest that liquidity provision via the SharesPost platform significantly influences the form of compensation paid to employees before IPO and reduces the amount of capital raised in a funding event that must be allocated to meet employee needs.
Keywords: G12; G14; G24; 650; private markets; market efficiency; information asymmetry; IPO